Networking and telecommunications : concepts, methodologies, tools, and applications - Information Resources Management Association (Hershey, PA : Information Science Reference, 2010)
'This multiple-volume publications exhibits the most up-to-date collection of research results and recent discoveries in the transfer of knowledge access across the globe'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Computer networks; Telecommunication